The transition of a mental health facility to a COVID-19 isolation ward and unit to deliver remote inpatient mental health care - Keogh, Brian; Donohue, Gráinne (My University, 2022)
Throughout the COVID-19 pandemic, mental health services were confronted with significant challenges and mental health staff have not only had to provide a continued service for, often distressed, service users but have had to adapt practice and comply with the ever-changing public guidelines for containing the virus. There is a pressing need, therefore, to learn from the challenges that mental health services have faced and continue to face throughout different stages of the pandemic. While uncertainty is inevitable in pandemics, mental health nurses as a community can learn from individual experiences of adaptation. This article describes the unique and rapid transition of one Irish mental health facility to a COVID-19 isolation ward and unit for delivery of remote admission to a mental health service (home care admission). In order to capture this transitory experience, the areas discussed include preparation of the site, key challenges and the role of nursing staff, mental health service delivery, managing home care packages, the nurse management role and remote ward nursing. This discussion demonstrates how one mental health setting successfully evolved and met the challenges brought by the global pandemic through a combination of adaptability and flexibility in service delivery.
PUBLISHED
Keywords: COVID-19; Mental health nursing; Nurse leadership